Approaches to language, culture, and cognition the intersection of cognitive linguistics and linguistic anthropology - Yamaguchi, Masataka; Tay, Dennis; Blount, Benjamin; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Approaches to Language, Culture and Cognition aims to bring cognitive linguistics and linguistic anthropology closer together, calling for further investigations of language and culture from cognitively-informed perspectives against the backdrop of the current trend of linguistic anthropology.
Keywords: Social sciences; Ethnology; Philosophy